Genetic variation in aryl N‐acetyltransferase results in significant differences in the pharmacokinetic and safety profiles of amifampridine (3, 4‐diaminopyridine) phosphate. Issue 1 (9th December 2014) - Haroldsen, Peter E.; Garovoy, Marvin R.; Musson, Donald G.; Zhou, Huiyu; Tsuruda, Laurie; Hanson, Boyd; O'Neill, Charles A.
Abstract The clinical use of amifampridine phosphate for neuromuscular junction disorders is increasing. The metabolism of amifampridine occurs via polymorphic aryl N‐acetyltransferase (NAT), yet its pharmacokinetic (PK) and safety profiles, as influenced by this enzyme system, have not been investigated. The objective of this study was to assess the effect of NAT phenotype and genotype on the PK and safety profiles of amifampridine in healthy volunteers (N = 26). A caffeine challenge test and NAT2 genotyping were used to delineate subjects into slow and fast acetylators for PK and tolerability assessment of single, escalating doses of amifampridine (up to 30 mg) and in multiple daily doses (20 mg QID) of amifampridine. The results showed that fast acetylator phenotypes displayed significantly lower Cmax, AUC, and shorter t1/2 for amifampridine than slow acetylators. Plasma concentrations of the N‐acetyl metabolite were approximately twofold higher in fast acetylators. Gender differences were not observed. Single doses of amifampridine demonstrated dose linear PKs. Amifampridine achieved steady state plasma levels within 1 day of dosing four times daily. No accumulation or time‐dependent changes in amifampridine PK parameters occurred. Overall, slow acetylators reported 73 drug‐related treatment‐emergent adverse events versus 6 in fast acetylators. Variations in polymorphic NAT corresponding with fast and slow acetylator phenotypes significantly affects the PK and safety profiles of amifampridine.